Geochemistry of the Tanshan Oil Shale in Jurassic Coal Measures, Western Ordos Basin: Implications for Sedimentary Environment and Organic Matter Accumulation - Wei He; Shu Tao; Lianfu Hai; Rui Tao; Xiangcheng Wei; Lei Wang (Energies, 2022)
The Tanshan area is located in the southern section of the west margin of the Ordos basin. The Middle Jurassic Yan’an Formation is relatively thick and rich in coal and oil shale layers, having positive potential for energy development. In order to explore the sedimentary environment of oil shale and the controlling factors of organic matter accumulation, 18 oil shale samples collected from two boreholes (Guyou-3 and Guyou-4) in the Tanshan area were selected as the research objects, and organic geochemical and elemental geochemical tests were carried out systematically. The results show that oil shales have the characteristics of medium oil content, medium ash, high calorific value, low sulfur and low maturity stage, which constitutes good hydrocarbon generation potential. The organic matter is mainly humic type, resulting from terrigenous debris and higher plant debris. The indictors of C-value (mean 81.90), Th/U ratio (mean 3.44), CaO/(MgO·Al2 O3) ratio (mean 0.07), δEu (mean 0.71), δCe (mean 1.15), V/(V + Ni) ratio (mean 0.79), Ceanom index (mean −0.04), Babio index (mean 488.97 μg/g), P/Ti ratio (mean 0.08), TOC/S ratio (mean 59.80), Sr/Ba ratio (mean 0.57) and (La/Yb)N ratio (mean 14.71) indicate that Tanshan oil shales were formed in a warm–humid climate and anoxic-reducing environment, with a low-salinity water body and a low deposition rate but also a relatively low initial paleoproductivity. Paleoclimate conditions, organic matter sources and redox properties of paleowater are the main controlling factors affecting the accumulation of organic matter in oil shales. Although low paleoproductivity and deposition rates are not conducive to the preservation of organic matter, under the conditions of warm and humid climate and a reducing water environment, the continuous and stable input of terrigenous debris and higher plant debris can also cause the enrichment of organic matter.